TỔNG HỢP MỘT SỐ gem-DIAXETAT XÚC TÁC TRIFLAT LITIUM TRONG ĐIỀU KIỆN HÓA HỌC XANH - Ngọc hạnh, Lê Thị; Thạch, Lê Ngọc (Vietnam Journal of Chemistry, 2012)
In this paper, the conversion of some aromatic aldehydes (benzaldehyde, vanilline) into corresponding gem-diacetates (acylals) was carried out in Green Chemistry conditions as under the irradiation of microwave (domestic and professional oven) or ultrasound (ultrasonic bath), in the solvent-free media, and catalysis by new generation of Lewis acid (lithium triflate). The results showed that the rate and the yield of these reactions increased when compared with conventional heating. By-products (from Fries rearrangement of triacetate of vanilline) was observed when vanilline was converted into triacetate with conventional heating. However it was disappeared when the reaction was performed in microwave oven or ultrasonic bath. Keywords: gem-diacetate, Green Chemistry, benzaldehyde, vanilline, microwave chemistry, sonochemistry, solvent-free.